The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fneur.2022.905998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neuroimaging Patterns for the Detection of Atrial Fibrillation by Implantable Loop Recorders in Patients With Embolic Stroke of Undetermined Source

Abstract: ObjectivesA trial fibrillation (AF) is a well-known etiology of embolic stroke of undetermined source (ESUS), although the optimal detection strategy of AF was not been fully evaluated yet. We assessed AF detection rate by implantable loop recorder (ILR) in patients with ESUS and compared the clinical characteristics and neuroimaging patterns between the patients with AF and AF-free patients.MethodsWe reviewed clinical characteristics and neuroimaging patterns of consecutive patients with who were admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…The AF/AFL detection rate in our cohort was similar or relatively higher than in previous studies, which showed that most AF detections by ILR occurred during the first few months [8][9][10][11][12]; however, the cumulative incidence of AF detection continued to increase over a year, albeit slowly. Our study results were also consistent with these findings, but the most distinct observation from our study population was that the interval from the index stroke to ILR implant was remarkably long [3,4,[9][10][11][12][13]. This is not only because of the different study design and population in our study, but also because ILR implants were reimbursed for only recurrent stroke until November 2018 in Korea.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The AF/AFL detection rate in our cohort was similar or relatively higher than in previous studies, which showed that most AF detections by ILR occurred during the first few months [8][9][10][11][12]; however, the cumulative incidence of AF detection continued to increase over a year, albeit slowly. Our study results were also consistent with these findings, but the most distinct observation from our study population was that the interval from the index stroke to ILR implant was remarkably long [3,4,[9][10][11][12][13]. This is not only because of the different study design and population in our study, but also because ILR implants were reimbursed for only recurrent stroke until November 2018 in Korea.…”
Section: Discussionsupporting
confidence: 76%
“…There is a clinical significance of AF/AFL detection in CS patients because it has an impact on secondary stroke prevention, which is possibly associated with higher anticoagulation incidence, although controversial [6,7]. The AF/AFL detection rate in our cohort was similar or relatively higher than in previous studies, which showed that most AF detections by ILR occurred during the first few months [8][9][10][11][12]; however, the cumulative incidence of AF detection continued to increase over a year, albeit slowly. Our study results were also consistent with these findings, but the most distinct observation from our study population was that the interval from the index stroke to ILR implant was remarkably long [3,4,[9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 52%
“…Ischemic lesion patterns well represent the stroke mechanism, and a recent study showed that a large territorial infarction in a single vascular territory pattern was associated with AF detection in ESUS patients receiving ILR. 23 Paroxysmal AF related-strokes showed larger lesions and higher NIHSS scores than aortic arch atheroma or PFO related strokes, explained by the large brin containing clot formed from the left atrium. 24 In comparison to stoke related to PFO, strokes related to AF showed con uent lesion with additional small lesions, as PFOs may work as lters, allowing only smaller emboli to pass through the shunt.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to previous studies, our main focus was to identify the neuroimaging patterns associated with the diagnostic yield of AF in patients with ESUS who received ILR. Yushan et al found that a neuroimaging profile of bilateral infarcts was associated with AF detection using insertable cardiac monitor in ESUS patients ( 18 ) while Kim et al demonstrated a higher AF detection rate associated with whole-territory infarction on brain imaging ( 19 ). Makimoto et al ( 20 ) previously reported that posterior cerebral artery stroke but not in the territory of the vertebral artery may be more frequently related to AF than other stroke localizations in ESUS.…”
Section: Discussionmentioning
confidence: 99%